Summer of two wishes [large type] - London, Julia (Thorndike/Chivers, 2009)
Macy Lockhart's life shattered in a moment with the news that her husband, Finn, serving in the military overseas has been killed in the line of duty. Their ardent marriage is over, leaving Macy alone, empty, directionless. But while she tries to sustain herself with memories of Finn, who made her and their small Texas ranch the center of his life, it is wealthy Wyatt Clark who slowly brings joy back into her life. Until Finn miraculously returns home.